Perkawinan Dalam Perspektif Hukum Islam dan Hukum Positif - Tasyukur; Yustisi, Nabhani (ENLEKTURER: Journal of Islamic Studies, 2024)
Marriage in Islamic law and positive law creates various issues within society, leading to many individuals not fulfilling administrative requirements as stipulated by law. For instance, marriages must be registered at the Office of Religious Affairs, and divorces must be processed through the Religious Court. Based on these problems, the author is interested in examining "Marriage in the Perspective of Islamic Law and Positive Law." The research method used is a normative juridical analysis, which analyzes legal materials based on applicable regulations as positive law norms and Islamic law. A marriage is considered valid if it meets the conditions and pillars set out in religious provisions. The difference in marriage in Islamic law emphasizes the principles of justice, responsibility, and the protection of individual and family rights, while positive law emphasizes legal certainty and administrative order.